Composite photocatalytic material, preparation method and application thereof
Patent Information
- Application Number
- CN202611224579.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-13
- Publication Date
- 2026-10-23
- Estimated Expiration
- 2046-08-13
AI Technical Summary
[0004]然而,现有g-C3N4/ZnO复合光催化材料在实际废水处理中仍存在不足
[0031]根据本申请,g-C3N4/ZnO复合光催化基底用于在光照条件下产生活性物种并降解土霉素;HEMAP-SBMA共聚物改性层通过低负载、非连续的界面调控方式,提高ZnO表面稳定性并降低Zn2+浸出风险,同时利用SBMA两性离子单元形成亲水水化界面,减少复杂废水中腐殖酸、蛋白质、多糖等大分子有机物对活性表面的覆盖。由于该改性层不形成致密包覆层,土霉素、溶解氧和水仍可向光催化界面传质,因此该材料适合用于含土霉素废水的持续光催化处理,并有利于提高循环使用稳定性、抗污染能力和出水安全性。
Smart Images

Figure CN122745962B_ABST
Abstract
Description
Technical Field
[0001] This application relates to the field of photocatalyst technology, specifically to a composite photocatalytic material, its preparation method, and its application. Background Technology
[0002] With the development of the pharmaceutical and aquaculture industries, tetracycline antibiotics such as oxytetracycline are used extensively. Once these antibiotics enter the aquatic environment, due to their stable molecular structure and poor biodegradability, they easily remain in water bodies and sediments, and may induce the spread of drug-resistant bacteria and genes, posing potential risks to the ecological environment and human health.
[0003] Semiconductor photocatalysis technology utilizes light energy to excite catalysts to generate electrons and holes, further producing reactive species such as superoxide radicals and hydroxyl radicals, thereby achieving the oxidative degradation of organic pollutants. ZnO has advantages such as low cost, simple preparation, and strong oxidizing power, making it one of the commonly used photocatalytic materials. g-C3N4 has certain visible light response capabilities, good chemical stability, and readily available raw materials. Combining g-C3N4 with ZnO to form a heterojunction can, to a certain extent, promote the separation of photogenerated electrons and holes, improving the degradation performance of organic pollutants such as oxytetracycline.
[0004] However, existing g-C3N4 / ZnO composite photocatalytic materials still have shortcomings in practical wastewater treatment. Although the composite substrate composed of g-C3N4 and ZnO can form a heterogeneous structure that is conducive to the separation of photogenerated carriers, during the aqueous photocatalytic cycle, the ZnO surface is easily affected by repeated light exposure, water flow, and water quality, leading to changes in the surface state, such as Zn... 2+ Leaching further affects the sustained photocatalytic degradation effect of the material and the quality of the effluent. Therefore, for this type of composite photocatalytic material, it is not enough to simply improve the photoresponse performance of the g-C3N4 / ZnO substrate itself; it is also necessary to stabilize and regulate the adjacent reaction interface on the ZnO surface. Summary of the Invention
[0005] This application provides a composite photocatalytic material, its preparation method, and its application. A HEMAP-SBMA copolymer is introduced onto the surface of a g-C3N4 / ZnO composite photocatalytic substrate. The phosphorus-containing groups in the HEMAP unit coordinate and anchor with the Zn sites on the ZnO surface, reducing the dissolution of ZnO and the degradation of Zn during the treatment of oxytetracycline wastewater. 2+ Leaching; at the same time, the zwitterionic structure of sulfobetaine in the SBMA unit forms a hydration interface on the material surface, reducing the non-specific coverage of macromolecular organic matter such as humic acid and protein, and improving the material's anti-fouling ability, cycle stability and continuous photocatalytic degradation efficiency.
[0006] In a first aspect, this application provides a method for preparing a composite photocatalytic material, characterized by comprising the following steps: S1. Prepare ZnO powder and g-C3N4 powder, mix the ZnO powder and the g-C3N4 powder and calcine them to obtain g-C3N4 / ZnO composite photocatalytic substrate; S2. 2-Methyl-2-acrylate-2-hydroxyethyl ester phosphate (HEMAP) and methacryloyl ethyl sulfobetaine (SBMA) are mixed in a solvent, and after purging with an inert gas to remove oxygen, a free radical initiator is added to carry out a copolymerization reaction. After purification and drying, HEMAP-SBMA copolymer is obtained. S3. The g-C3N4 / ZnO composite photocatalytic substrate is dispersed in a solvent, and the HEMAP-SBMA copolymer is added to allow the phosphorus-containing groups in the HEMAP-SBMA copolymer to coordinate and anchor with the Zn sites on the ZnO surface, thereby obtaining an intermediate product; S4. The intermediate product is washed and dried to remove unanchored or weakly adsorbed HEMAP-SBMA copolymer, thereby obtaining HEMAP-SBMA copolymer modified g-C3N4 / ZnO composite photocatalytic material.
[0007] According to this application, in order to solve the problems of insufficient stability of ZnO and Zn 2+ To address the leaching issue, the inventors first introduced a phosphorus-containing anchoring structure onto the g-C3N4 / ZnO surface, capable of binding to Zn sites on the ZnO surface. Phosphorus-containing groups typically form relatively stable interfacial interactions with metal oxide surfaces, which, compared to ordinary physically adsorbed organic modifiers, is more conducive to maintaining the adhesion stability of the modified layer during washing, stirring, and recycling. Based on this, this application selected 2-methyl-2-acrylate-2-hydroxyethyl phosphate as the source of the phosphorus-containing polymerizable monomer, enabling its subsequent introduction into the copolymer that can be immobilized on the g-C3N4 / ZnO surface via polymerization.
[0008] However, the inventors further discovered that while modifying g-C3N4 / ZnO with only HEMAP or other phosphorus-containing polymers formed from phosphorus monomers can enhance the bonding between the modified component and the ZnO surface, it may also introduce new interface problems. On the one hand, phosphorus-containing groups have strong polarity and a certain coordination ability. If they are excessively enriched near the ZnO surface, they can easily lead to excessively strong local interface polarity, increasing the occupation of the photocatalytic interface by non-reactive components. On the other hand, too many phosphorus-containing groups near the ZnO surface may also shield or passivate some surface active sites, affecting the entry of oxytetracycline, dissolved oxygen, and water molecules into the g-C3N4 / ZnO reaction interface. In other words, although a single phosphorus-containing anchoring structure can improve the fixation stability of the modified layer, it cannot simultaneously guarantee the openness of the photocatalytic reaction interface and its adaptability to the aqueous phase.
[0009] To address the issues of excessive interfacial polarization and limited reaction interfaces caused by the single phosphorus-containing anchoring modification, the inventors further introduced methacryloyl ethyl sulfobetaine (SBMA). The SBMA unit has an amphoteric structure and can form hydration segments in an aqueous environment, thereby modulating the hydrophilic state of the region adjacent to the ZnO surface. This hydration segment does not exist as an independent antifouling coating, but rather serves to mitigate the high polarity interface that the HEMAP phosphorus-containing anchoring unit may cause near the ZnO surface, maintaining a relatively loose, hydrophilic interface near the ZnO that facilitates reactant access, thus reducing the risk of interfacial shielding due to excessive enrichment of phosphorus-containing groups.
[0010] Furthermore, instead of adding HEMAP and SBMA as two separate components to the g-C3N4 / ZnO system, the inventors first allowed HEMAP and SBMA to undergo free radical copolymerization to form a HEMAP-SBMA copolymer. The reason for this design is that if SBMA-type polymers are added alone, they mainly rely on physical adsorption or weak interfacial interactions to remain on the g-C3N4 / ZnO surface, making them prone to desorption during washing, stirring, and recycling, and difficult to continuously regulate the aqueous interface on the ZnO surface. Conversely, if only HEMAP-type phosphorus-containing polymers are used, the aforementioned problems of excessive interfacial polarization and limited active sites are likely to occur. By connecting the HEMAP anchoring unit and the SBMA hydration unit in the same copolymer segment, the HEMAP unit can confine the copolymer to the vicinity of the ZnO surface, while the SBMA unit regulates the hydration interface around this anchoring position. Both work together within the same polymer system.
[0011] Therefore, the HEMAP-SBMA copolymer in this application is not simply a parallel mixture of phosphorus-containing anchoring materials and zwitterionic materials. Instead, it utilizes HEMAP units to address the issue of easy desorption of SBMA hydration segments, while simultaneously using SBMA units to mitigate the potential for excessive interfacial polarization and localized shading caused by the HEMAP phosphorus-containing anchoring units. The two components synergistically interact through the copolymer structure, ensuring that the modified layer remains stably near the ZnO surface without forming a dense coating that isolates the g-C3N4 / ZnO photocatalytic substrate from the aqueous reaction system.
[0012] Furthermore, this application controls the addition ratio of the HEMAP-SBMA copolymer to the g-C3N4 / ZnO composite photocatalytic substrate in S3, and removes unanchored or weakly adsorbed copolymers by washing and drying in S4, so that the copolymers ultimately retained on the material surface are mainly the portions that coordinate with the ZnO surface through HEMAP units. This treatment method is beneficial for forming a low-load anchored hydration interface, rather than an organic coating structure.
[0013] Therefore, the HEMAP-SBMA copolymer-modified g-C3N4 / ZnO composite photocatalytic material prepared in this application can improve the stability of the reaction interface adjacent to the ZnO surface and the water phase adaptability while maintaining effective contact between the g-C3N4 / ZnO substrate and light, water, dissolved oxygen and oxytetracycline, thereby improving the continuous photocatalytic degradation effect of the material in water containing oxytetracycline.
[0014] In some embodiments, the method for preparing the ZnO powder in step S1 includes the following steps: Zinc nitrate hexahydrate and urea were dissolved in water to form a mixed solution. The mixed solution was transferred to a hydrothermal reactor and reacted at 180–240°C for 20–30 h. After the precipitate was cooled to room temperature, it was washed repeatedly with pure water and ethanol alternately. After drying, it was calcined at 500–650°C for 1–3 h to obtain ZnO powder. The molar ratio of zinc nitrate hexahydrate to urea was 1:1 to 1:4.
[0015] In some of the methods described above, zinc nitrate hexahydrate is reacted with urea under hydrothermal conditions, followed by washing, drying, and calcination to obtain ZnO powder. This step serves to provide a relatively stable ZnO component in terms of composition and morphology for the subsequent g-C3N4 / ZnO composite substrate. During the hydrothermal process, urea gradually releases an alkaline environment, which is beneficial for the uniform conversion of the zinc source into the ZnO precursor. The subsequent calcination treatment helps improve the crystallinity and structural stability of ZnO. By limiting the hydrothermal temperature, reaction time, calcination temperature, and the molar ratio of zinc source to urea within a reasonable range, batch fluctuations in ZnO preparation can be reduced, making the obtained ZnO more suitable for composite formation with g-C3N4 / ZnO.
[0016] In some embodiments, the molar ratio of zinc nitrate hexahydrate to urea is 1:2.
[0017] In some of the above methods, controlling the molar ratio of the two to 1:2 is beneficial for forming a more uniform and stable ZnO powder during the hydrothermal process.
[0018] In some embodiments, the preparation method of the g-C3N4 powder in step S1 includes the following steps: Urea was placed in a crucible and calcined at 500–580°C for 1–4 hours. After cooling to room temperature, it was washed several times with pure water and ethanol alternately. Then it was dried in an oven at 55°C for 12 hours and ground evenly in a mortar to obtain g-C3N4 powder.
[0019] Among the methods mentioned above, the urea thermal polymerization method uses readily available raw materials and has a simple process, which can form a g-C3N4 component with a certain visible light response capability; subsequent washing and drying help remove residual small molecules and by-products, while grinding treatment helps improve the uniformity of the powder.
[0020] In some embodiments, in step S1, the mass ratio of ZnO powder to g-C3N4 powder is 1:0.3 to 1, the mixing method is grinding and mixing, and the grinding time is 20 to 60 minutes; the calcination temperature is 450 to 550°C, and the calcination time is 0.5 to 2 hours.
[0021] In some of the above methods, controlling the mass ratio of ZnO to g-C3N4 to 1:0.3 to 1 can ensure the basic photocatalytic activity of ZnO while introducing an appropriate amount of g-C3N4 to form a composite interface, which promotes the separation of photogenerated carriers. Grinding and mixing are conducive to full contact between the two, and subsequent calcination at 450 to 550℃ helps to improve the stability of the interface bonding.
[0022] In some implementations, S2 includes the following steps: 2-Methyl-2-acrylate-2-hydroxyethyl ester phosphate and methacryloylethyl sulfobetaine were added to a solvent in a molar ratio of 1:3 to 1:8 and stirred to dissolve, thus obtaining a monomer mixture. After purging nitrogen or argon into the monomer mixture to remove oxygen for 30-60 minutes, a free radical initiator is added, and a free radical copolymerization reaction is carried out at 50-80°C for 6-12 hours under inert gas protection to obtain a reaction solution. The reaction solution is subjected to dialysis, ultrafiltration, precipitation or centrifugal washing to remove unreacted monomers and small molecule impurities, and then dried to obtain HEMAP-SBMA copolymer.
[0023] Among the aforementioned methods, a molar ratio range of 1:3 to 1:8 is beneficial for forming an appropriate amount of phosphorus-containing anchoring units and sufficient sulfobetaine zwitterionic units in the copolymer. This allows the resulting copolymer to both coordinate and anchor with Zn sites on the ZnO surface and to form a hydrophilic hydration regulation effect on the material surface. HEMAP content within this range provides surface immobilization capability for the copolymer, while SBMA content enhances the hydration interface characteristics. The combination of these two factors makes the copolymer suitable for subsequent low-loading, discontinuous distribution on the surface of the g-C3N4 / ZnO composite photocatalytic substrate, thereby reducing Zn content. 2+ It provides a material basis for leaching, improving surface antifouling capabilities in complex water bodies, and maintaining mass transfer channels.
[0024] In some implementations, S3 includes the following steps: The g-C3N4 / ZnO composite photocatalytic substrate was added to a solvent and then subjected to stirring, ultrasonication, or a combination of stirring and ultrasonication to achieve uniform dispersion, thereby obtaining a substrate dispersion. HEMAP-SBMA copolymer is added to the substrate dispersion, wherein the mass ratio of the g-C3N4 / ZnO composite photocatalytic substrate to the HEMAP-SBMA copolymer is 100:0.5 to 100:5. The pH of the system is adjusted to 6 to 7.5, and the reaction is carried out at 20 to 40°C for 4 to 8 hours. This allows the phosphorus-containing groups in the HEMAP-SBMA copolymer to coordinate and anchor with the Zn sites on the ZnO surface, and the zwitterionic units of sulfobetaine are distributed on the surface of the g-C3N4 / ZnO composite photocatalytic substrate, thus obtaining an intermediate product.
[0025] In some of the aforementioned methods, the mass ratio of the g-C3N4 / ZnO composite photocatalytic substrate to the HEMAP-SBMA copolymer is 100:0.5 to 100:5. This mass ratio range is beneficial for distributing the copolymer on the substrate surface with a low loading, allowing the phosphorus-containing groups to coordinate and anchor with the Zn sites on the ZnO surface, while simultaneously enabling the sulfobetaine zwitterionic units to form a hydrophilic hydration interface on the surface. A pH of 6–7.5 represents a relatively mild, near-neutral condition, which is beneficial for maintaining the structural stability of the g-C3N4 / ZnO substrate and promoting the interfacial interaction between the phosphorus-containing groups and the ZnO surface. The key to the reaction conditions is to fix the copolymer on the substrate surface with a low loading, rather than forming a thick layer or dense coating.
[0026] In some implementations, S4 includes the following steps: The intermediate product is subjected to solid-liquid separation, and the resulting solid is washed sequentially with water, ethanol or a water-ethanol mixture to remove HEMAP-SBMA copolymers that are not coordinated and anchored to Zn sites on the ZnO surface and weakly adsorbed HEMAP-SBMA copolymers. After washing, the solids are collected by centrifugation, vacuum filtration or filtration, and then vacuum dried at 40-70℃ to obtain HEMAP-SBMA copolymer modified g-C3N4 / ZnO composite photocatalytic material.
[0027] In some of the above methods, unanchored or weakly adsorbed HEMAP-SBMA copolymers are removed through solid-liquid separation, solvent washing, and drying. This step helps to retain the copolymer portion that forms a relatively stable coordination anchor with the Zn sites on the ZnO surface, so that the modified layer on the final material surface remains in a low-load, discontinuous state, rather than forming a free polymer accumulation or an organic coating layer. At the same time, washing with water, ethanol, or a water-ethanol mixed solvent can gently remove residual monomers, small molecule impurities, and weakly adsorbed polymers. Drying at 40–70°C is beneficial for obtaining structurally stable HEMAP-SBMA copolymer-modified g-C3N4 / ZnO composite photocatalytic materials that are easy to store and use.
[0028] Secondly, this application provides a composite photocatalytic material prepared according to the preparation method of any embodiment of the first aspect.
[0029] According to this application, the core structure of the prepared composite photocatalytic material includes a g-C3N4 / ZnO composite photocatalytic substrate and a HEMAP-SBMA copolymer modified layer distributed on the substrate surface. This modified layer is formed by the coordination and anchoring of phosphorus-containing groups in the HEMAP-SBMA copolymer with Zn sites on the ZnO surface, and exists as a low-load interfacial layer rather than forming a coating layer. Therefore, the material can utilize the phosphorus-containing groups to improve the adhesion stability of the copolymer on the ZnO surface, reducing ZnO erosion and Zn... 2+ On the one hand, there is the risk of leaching; on the other hand, the zwitterionic units of SBMA can form a hydrated antifouling interface on the material surface, reducing the non-specific coverage of macromolecular organic matter such as humic acid, proteins, and polysaccharides. Simultaneously, because this modified layer has a low-load structure, oxytetracycline, dissolved oxygen, and water can still contact the g-C3N4 / ZnO photocatalytic interface, thereby improving the material's cycle stability and applicability to complex wastewaters while maintaining photocatalytic mass transfer and light contact conditions.
[0030] Thirdly, this application provides the application of composite photocatalytic materials prepared according to the preparation method of any embodiment of the first aspect in the photocatalytic degradation of antibiotic wastewater containing oxytetracycline.
[0031] According to this application, the g-C3N4 / ZnO composite photocatalytic substrate is used to generate active species and degrade oxytetracycline under light conditions; the HEMAP-SBMA copolymer modified layer improves the surface stability of ZnO and reduces Zn through a low-load, discontinuous interface regulation method. 2+This reduces the risk of leaching and utilizes SBMA zwitterionic units to form a hydrophilic hydration interface, minimizing the coverage of the active surface by large organic molecules such as humic acid, proteins, and polysaccharides in complex wastewater. Because this modified layer does not form a dense coating, oxytetracycline, dissolved oxygen, and water can still transfer mass to the photocatalytic interface. Therefore, this material is suitable for the continuous photocatalytic treatment of oxytetracycline-containing wastewater and helps improve its recycling stability, anti-fouling ability, and effluent safety.
[0032] Compared with the prior art, the beneficial effects of this application are at least as follows: 1. To address the issue of insufficient stability of the ZnO surface in aqueous photocatalytic cycling when g-C3N4 / ZnO is used for oxytetracycline wastewater treatment, this application does not employ conventional thick-layer coating, inorganic passivation, or simple phosphate treatment methods. Instead, it uses HEMAP-SBMA copolymer to perform low-load interface regulation on the g-C3N4 / ZnO surface, causing the phosphorus-containing groups in the copolymer to coordinate and anchor with the Zn sites on the ZnO surface. This results in the polymer being mainly located at the ZnO adjacent interface, rather than forming a continuous isolation layer outside the photocatalytic substrate.
[0033] 2. The design of the HEMAP-SBMA copolymer in this application is not simply to improve the adhesion between the polymer and the substrate, nor is it a simple superposition of the known effects of phosphorus-containing monomers and zwitterionic monomers. Instead, HEMAP and SBMA units are linked within the same copolymer segment. The HEMAP unit provides a positioning function for the ZnO adjacent interface, while the SBMA unit regulates the hydration state and interfacial openness of this positioning region. Together, they enable the modified polymer to participate in the construction of the g-C3N4 / ZnO photocatalytic reaction interface with a low loading, thereby improving the material's cycle stability and continuous degradation effect during oxytetracycline water treatment. Attached Figure Description
[0034] The accompanying drawings, which are incorporated in and form part of this specification, illustrate embodiments consistent with this application and, together with the description, serve to explain the principles of this application.
[0035] Figure 1 The XPS full spectrum of the HEMAP-SBMA copolymer-modified g-C3N4 / ZnO composite photocatalyst material prepared in Example 1 of this application is shown. Detailed Implementation
[0036] The various embodiments or implementation schemes in this specification are described in a progressive manner, with each embodiment focusing on the differences from other embodiments.
[0037] In the description of this specification, the references to terms such as "one embodiment," "some embodiments," "illustrative embodiment," "example," "specific example," or "some examples," etc., indicate that a specific feature, structure, material, or characteristic described in connection with an embodiment or example is included in at least one embodiment or example of this application. In this specification, the illustrative expressions of the above terms do not necessarily refer to the same embodiment or example. Furthermore, the specific features, structures, materials, or characteristics described may be combined in any suitable manner in one or more embodiments or examples.
[0038] Furthermore, the terms "first" and "second" are used for descriptive purposes only and should not be construed as indicating or implying relative importance or implicitly specifying the number of technical features indicated. Thus, a feature defined as "first" or "second" may explicitly or implicitly include at least one of that feature. In the description of this application, "multiple" means at least two, such as two, three, etc., unless otherwise explicitly specified.
[0039] In this specification, unless otherwise specified, "parts" refers to "parts by weight".
[0040] The following describes embodiments of this application. The embodiments described below are exemplary and are only used to explain this application, and should not be construed as limiting this application. Where specific techniques or conditions are not specified in the embodiments, they are performed according to the techniques or conditions described in the literature in this field or according to the product instructions. Reagents or instruments used, unless otherwise specified, are all conventional products that can be obtained commercially.
[0041] 2-Methyl-2-acrylate-2-hydroxyethyl phosphate, CAS: 52628-03-2; Methacrylethyl sulfobetaine, CAS: 3637-26-1.
[0042] Preparation Example 1 Preparation of g-C3N4 / ZnO composite photocatalytic substrate: Weigh 11.9 parts of zinc nitrate hexahydrate, add it to 300 parts of deionized water, and stir for 15 min to completely dissolve it, obtaining a zinc salt solution; separately weigh 4.8 parts of urea, add it to 200 parts of deionized water, and stir to dissolve it, obtaining a urea solution; mix the above zinc salt solution and urea solution, continue stirring for 30 min, and then transfer it to a polytetrafluoroethylene-lined stainless steel hydrothermal reactor, and hydrothermally react at 220℃ for 24 h; after the reaction is completed, allow it to cool naturally to room temperature, collect the precipitate, and wash it three times each with deionized water and anhydrous ethanol; place the washed precipitate in a 55℃ oven to dry for 12 h, and then place it in a muffle furnace, raise the temperature to 600℃ at a rate of 10℃ / min, and calcine for 2 h to obtain ZnO powder; Twenty parts of urea were weighed and placed in a covered crucible. The crucible was placed in a muffle furnace and heated to 550°C at a rate of 10°C / min. The mixture was calcined for 2 hours and then allowed to cool naturally to room temperature. The resulting solid was washed three times alternately with deionized water and anhydrous ethanol, and then dried in a 55°C oven for 12 hours. After drying, the solid was ground evenly in a mortar to obtain g-C3N4 powder. Weigh out 2 parts of ZnO powder and 1 part of g-C3N4 powder, place them in an agate mortar and grind for 30 min to ensure thorough mixing; place the mixed powder in a crucible and calcine in a muffle furnace at a heating rate of 5℃ / min to 500℃ for 1 h. After natural cooling, grind to obtain the g-C3N4 / ZnO composite photocatalytic substrate.
[0043] Example 1 Preparation of composite photocatalytic materials: Weigh 2.1 parts HEMAP and 14 parts SBMA (the molar ratio of HEMAP to SBMA is approximately 1:5), add the two monomers to 300 parts of a deionized water / ethanol mixed solvent (the volume ratio of deionized water to ethanol is 4:1), and stir until completely dissolved to obtain a monomer mixture. Purge the monomer mixture with nitrogen gas for 45 min to remove dissolved oxygen, then add 0.16 parts ammonium persulfate as a free radical initiator. Under nitrogen protection, heat the reaction system to 65°C and stir for 8 h. After the reaction is complete, allow it to cool naturally to room temperature. Place the reaction solution into a dialysis bag with a molecular weight cutoff of 1000 Da and dialyze with deionized water for 48 h, changing the deionized water every 6-8 h to remove unreacted monomers and small molecule impurities. After dialysis, freeze-dry the dialysate to obtain the HEMAP-SBMA copolymer. Three parts of the g-C3N4 / ZnO composite photocatalytic substrate prepared in Preparation Example 1 were weighed and added to 600 parts of a deionized water / ethanol mixed solvent with a volume ratio of deionized water to ethanol of 4:1. The mixture was first magnetically stirred for 10 min and then ultrasonically dispersed for 15 min to obtain a uniform substrate dispersion. 0.08 parts of the HEMAP-SBMA copolymer were weighed and added to the above substrate dispersion to make the mass ratio of g-C3N4 / ZnO substrate to HEMAP-SBMA copolymer 100:2.7. The pH of the system was adjusted to 7.0, and the mixture was magnetically stirred at 25 °C for 6 h to allow the phosphorus-containing groups in the HEMAP-SBMA copolymer to coordinate and anchor with the Zn sites on the ZnO surface, thus obtaining an intermediate product. The intermediate product was centrifuged at 8000 rpm for 5 min. The supernatant was discarded. The resulting solid was washed three times each with deionized water and anhydrous ethanol. The washed solid was then redispersed in deionized water, lightly sonicated for 3 min, and then centrifuged again to remove unanchored or weakly adsorbed copolymers. The resulting solid was dried in a vacuum drying oven at 55℃ for 12 h to obtain the HEMAP-SBMA copolymer modified g-C3N4 / ZnO composite photocatalytic material.
[0044] like Figure 1 As shown, the XPS full spectrum of the HEMAP-SBMA copolymer-modified g-C3N4 / ZnO composite photocatalyst material exhibits characteristic signals of elements such as C, N, O, and Zn, indicating the presence of g-C3N4 and ZnO components in the material. Simultaneously, weak P and S elemental signals were observed in the low binding energy region, originating from the phosphorus-containing groups in HEMAP and the sulfonic acid groups in SBMA, respectively. The relatively low P and S signal intensities indicate a limited amount of copolymer introduced onto the composite substrate surface, consistent with the low proportion of HEMAP-SBMA copolymer added during preparation. These results demonstrate that the HEMAP-SBMA copolymer has been successfully introduced onto the surface of the g-C3N4 / ZnO composite substrate.
[0045] Example 2 Preparation of composite photocatalytic materials: The method is largely the same as in Example 1, except that 0.08 parts of HEMAP-SBMA copolymer are replaced with 0.015 parts of HEMAP-SBMA copolymer.
[0046] Example 3 Preparation of composite photocatalytic materials: The method is largely the same as in Example 1, except that 0.08 parts of HEMAP-SBMA copolymer are replaced with 0.15 parts of HEMAP-SBMA copolymer.
[0047] Comparative Example 1 Preparation of composite photocatalytic materials: Weigh 12.6 parts of HEMAP and add them to 300 parts of a deionized water / ethanol mixed solvent (deionized water to ethanol volume ratio 4:1). Stir to dissolve. Purge the solution with nitrogen gas for 45 min, add 0.13 parts of ammonium persulfate, and react at 65 °C for 8 h under nitrogen protection. After the reaction is complete, dialyze the reaction solution through a dialysis bag with a molecular weight cutoff of 1000 Da for 48 h, and then freeze-dry to obtain polyHEMAP. Weigh 3 parts of the g-C3N4 / ZnO composite photocatalytic substrate prepared in Preparation Example 1, add it to 600 parts of deionized water / ethanol mixed solvent, stir and ultrasonically disperse; Add 0.08 parts of polyHEMAP, adjust the pH of the system to 7.0, and stir at 25°C for 6 hours to allow the phosphorus-containing groups in the polyHEMAP to coordinate and anchor with the Zn sites on the ZnO surface. After the reaction was completed, the product was centrifuged at 8000 rpm for 5 min. The supernatant was discarded, and the obtained solid was washed three times each with deionized water and anhydrous ethanol. The washed solid was then redispersed in deionized water, lightly sonicated for 3 min, and then centrifuged to collect the solid to remove unanchored or weakly adsorbed copolymers. The obtained solid was then dried in a vacuum drying oven at 55℃ for 12 h to obtain polyHEMAP modified g-C3N4 / ZnO material as a composite photocatalytic material.
[0048] Comparative Example 2 Preparation of composite photocatalytic materials: Weigh 16.8 parts of SBMA, add 300 parts of deionized water, and stir to dissolve; purge the solution with nitrogen for 45 min, add 0.17 parts of ammonium persulfate, and react at 65 °C for 8 h under nitrogen protection. After the reaction is completed, dialyze the reaction solution through a dialysis bag with a molecular weight cutoff of 1000 Da for 48 h, and then freeze dry to obtain polySBMA. Weigh 3 parts of the g-C3N4 / ZnO composite photocatalytic substrate prepared in Preparation Example 1, add it to 600 parts of deionized water / ethanol mixed solvent, stir and ultrasonically disperse; Add 0.08 parts of polySBMA, adjust the pH of the system to 7.0, and stir at 25°C for 6 hours to distribute polySBMA on the surface of the g-C3N4 / ZnO composite photocatalytic substrate; After the reaction was completed, the product was centrifuged at 8000 rpm for 5 min. The supernatant was discarded, and the obtained solid was washed three times each with deionized water and anhydrous ethanol. The washed solid was then redispersed in deionized water, lightly sonicated for 3 min, and then centrifuged to collect the solid to remove unanchored or weakly adsorbed copolymers. The obtained solid was then dried in a vacuum drying oven at 55℃ for 12 h to obtain polySBMA-modified g-C3N4 / ZnO material as a composite photocatalytic material.
[0049] Comparative Example 3 Preparation of composite photocatalytic materials: Weigh 3 parts of the g-C3N4 / ZnO composite photocatalytic substrate prepared in Preparation Example 1, add it to 600 parts of deionized water / ethanol mixed solvent, and ultrasonically disperse for 15 min; Add 0.01 parts of the polyHEMAP prepared in Comparative Example 1, adjust the pH of the system to 7.0, and stir at 25°C for 6 h to allow the phosphorus-containing groups in the polyHEMAP to coordinate and anchor with the Zn sites on the ZnO surface. After the reaction is complete, the product is centrifuged and the obtained solid is washed three times each with deionized water and anhydrous ethanol, and then vacuum dried at 55°C for 12 h to obtain the polyHEMAP premodified g-C3N4 / ZnO intermediate. The polyHEMAP premodified g-C3N4 / ZnO intermediate was added back into 600 parts of deionized water / ethanol mixed solvent and ultrasonically dispersed for 15 min; then 0.07 parts of the polySBMA prepared in Comparative Example 2 were added and stirred at 25 °C for 6 h. After the reaction was completed, the product was centrifuged at 8000 rpm for 5 min. The supernatant was discarded, and the obtained solid was washed three times each with deionized water and anhydrous ethanol. The washed solid was then redispersed in deionized water, lightly sonicated for 3 min, and then centrifuged to collect the solid to remove unanchored or weakly adsorbed copolymers. The obtained solid was then dried in a vacuum drying oven at 55℃ for 12 h to obtain the stepwise modified g-C3N4 / ZnO material as a composite photocatalytic material.
[0050] Comparative Example 4 Preparation of composite photocatalytic materials: Weigh 3 parts of the g-C3N4 / ZnO composite photocatalytic substrate prepared in Preparation Example 1, add it to 600 parts of deionized water / ethanol mixed solvent, and ultrasonically disperse for 15 min; Then, 0.01 parts of the polyHEMAP material prepared in Comparative Example 1 and 0.07 parts of the polySBMA prepared in Comparative Example 2 were added to the above dispersion, the pH of the system was adjusted to 7.0, and the mixture was stirred at 25°C for 6 h. After the reaction was completed, the product was centrifuged at 8000 rpm for 5 min. The supernatant was discarded, and the obtained solid was washed three times each with deionized water and anhydrous ethanol. The washed solid was then redispersed in deionized water, lightly sonicated for 3 min, and then centrifuged to collect the solid to remove unanchored or weakly adsorbed copolymers. The obtained solid was dried in a vacuum drying oven at 55℃ for 12 h to obtain the polyHEMAP / polySBMA physically modified g-C3N4 / ZnO material as a composite photocatalytic material.
[0051] Comparative Example 5 Preparation of composite photocatalytic materials: The method is largely the same as in Example 1, except that 0.08 parts of HEMAP-SBMA copolymer are replaced with 0.3 parts of HEMAP-SBMA copolymer.
[0052] Comparative Example 6 Preparation of composite photocatalytic materials: The g-C3N4 / ZnO composite photocatalytic substrate prepared in Preparation Example 1 was used as a composite photocatalytic material.
[0053] Test section Wastewater to be treated: Blank system: 30 mg / L oxytetracycline solution; Humic acid system: 30 mg / L oxytetracycline + 10 mg / L humic acid; Protein system: 30 mg / L oxytetracycline + 10 mg / L bovine serum albumin; Inorganic salt system: 30 mg / L oxytetracycline + 2 mmol / L CaCl2 + 2 mmol / L MgCl2 + 5 mmol / L NaCl + 5 mmol / L Na2SO4.
[0054] Oxytetracycline photocatalytic degradation performance test: A blank system was selected as the wastewater to be treated (oxytetracycline solution with a concentration of 30 mg / L). 100 mL of wastewater was used as a group, and 20 mg of the composite photocatalyst material prepared in each example and comparative example was added to each group. The system was first stirred in the dark for 30 min to reach adsorption-desorption equilibrium, and then the photocatalytic reaction was carried out under a xenon lamp for 120 min. Every 10 min, a 3 mL sample was taken, centrifuged to remove the photocatalyst, and the supernatant was measured using a UV-Vis spectrophotometer. The degradation rate η of the catalyst could then be calculated, and the measured concentration of oxytetracycline was C. t The concentration of oxytetracycline at the beginning of illumination was C0, and the degradation rate η was calculated using the following formula. The results are shown in Table 1.
[0055]
[0056] Zn 2+ Leaching test: After the above blank system underwent photocatalytic degradation for 120 min, it was left to stand for another 4 h. Then, the reaction solution was filtered through a 0.22 μm filter membrane, and the Zn content in the solution was determined by ICP-OES. 2+ Concentration, the result is Zn 2+ The leaching amount and the results are shown in Table 2.
[0057] Pollution resistance test in complex water bodies Humic acid system, protein system, and inorganic salt system were selected as wastewater to be treated in sequence. 100 mL of wastewater was taken from each system as a group. 20 mg of the composite photocatalytic material prepared in each example and comparative example was added to each group. The system was first stirred in the dark for 30 min to reach adsorption-desorption equilibrium. Then, the photocatalytic reaction was carried out under a xenon lamp for 120 min. After the reaction was completed, 3 mL of sample was taken and centrifuged to remove the photocatalyst. The photometric value of the supernatant was measured using a UV-Vis spectrophotometer. The degradation rate η1 of the catalyst could then be calculated. Dividing the degradation rate η1 of the blank system by the degradation rate η1 of the blank system yielded the degradation retention rate R. The degradation retention rate was calculated using the following formula, and the results are shown in Table 3.
[0058]
[0059] Table 1
[0060] Table 2
[0061] Table 3
[0062] As shown in Examples 1, 2, and 3, the amount of HEMAP-SBMA copolymer added to the surface of the g-C3N4 / ZnO composite photocatalytic substrate affects the photocatalytic degradation process of the material, and this effect does not simply increase monotonically with increasing copolymer addition. In Example 2, the amount of HEMAP-SBMA copolymer added was relatively low, resulting in fewer surface organic segments. Therefore, in the initial stage of the reaction, it had little impact on the light contact, active site exposure, and oxytetracycline molecule approach process of g-C3N4 / ZnO. The degradation rates at 30 min and 60 min were slightly higher than in Example 1 and close to those of the unmodified comparative example 6. However, due to the low copolymer loading, the distribution of HEMAP phosphorus-containing anchoring units and SBMA hydration units near the ZnO reaction interface was insufficient, limiting its effect on ZnO surface stabilization and continuous regulation of the aqueous interface. As the reaction time increased, the degradation growth rate gradually decreased compared to Example 1. In Example 3, the amount of HEMAP-SBMA copolymer added was higher than in Example 1, resulting in an increased distribution of phosphorus-containing anchoring units and hydration segments in the vicinity of the ZnO surface. Therefore, its effect on ZnO surface stabilization and interface maintenance in the later stages of the reaction was stronger than in Example 2, and the degradation rate at 120 min was higher than in Example 2. However, due to the further increase in the organic segment loading in Example 3, some light contact, exposure of active sites, or mass transfer processes of oxytetracycline and dissolved oxygen to the photocatalytic interface may be affected. Therefore, its initial degradation rate was lower than in Examples 1 and 2, and its final degradation rate was still lower than in Example 1. In Example 1, the amount of HEMAP-SBMA copolymer added was within a suitable range, effectively anchoring the ZnO surface in the vicinity of the HEMAP unit and regulating the hydration state of the anchored region through the SBMA unit, while not forming a significant organic layer that obscured the g-C3N4 / ZnO photocatalytic interface. Therefore, Example 1 maintained photocatalytic activity close to that of the unmodified substrate in the initial stage and exhibited better sustained degradation ability in the later stages of the reaction. This demonstrates that the modification effect of this application stems from the balance between the low-load interface regulation of the HEMAP-SBMA copolymer and the openness of the photocatalytic reaction interface, rather than simply increasing the copolymer loading.
[0063] As shown in Example 1 and Comparative Example 1, Comparative Example 1 used polyHEMAP alone to modify the g-C3N4 / ZnO composite photocatalytic substrate. PolyHEMAP contains phosphate groups, which can coordinate with Zn sites on the ZnO surface. Therefore, its Zn2+ leaching amount was significantly lower than that of the unmodified Comparative Example 6, indicating that the phosphorus-containing anchoring structure can indeed improve the surface stability of ZnO. The Zn2+ leaching amount in Example 1... 2+The leaching amount was at the same low level as Comparative Example 1, and slightly lower, indicating that the HEMAP units in the HEMAP-SBMA copolymer could still play a role in anchoring ZnO on the surface. Further analysis of the oxytetracycline degradation rate, the actual degradation rate under aqueous matrix interference conditions, and the recycling results shows that the main advantage of Example 1 compared to Comparative Example 1 is not simply a significant reduction in Zn content. 2+ Leaching, but while maintaining a low Zn content 2+ Simultaneously with the leaching level, the hydration state and interfacial openness of the HEMAP anchoring region are adjusted by the SBMA unit, allowing oxytetracycline, dissolved oxygen, and water molecules to better approach the reaction interface during continuous photocatalysis. Therefore, the sustained degradation effect of Example 1 is superior to that of Comparative Example 1, which is modified with a single polyHEMAP.
[0064] As shown in Example 1 and Comparative Example 2, Comparative Example 2 uses polySBMA to modify the g-C3N4 / ZnO composite photocatalytic substrate alone. The zwitterionic segments in polySBMA can improve the aqueous interface state of the material surface to some extent, thus its degradation retention under aqueous matrix interference conditions is improved compared to the unmodified Comparative Example 6. However, the polySBMA molecule lacks phosphorus-containing units that can coordinate and anchor with Zn sites on the ZnO surface, making it difficult to stably locate at the ZnO adjacent reaction interface, thus limiting its inhibitory effect on ZnO surface dissolution and Zn2+ leaching. Therefore, although Comparative Example 2 has a certain aqueous interface regulation effect, its Zn... 2+ The leaching amount and degradation retention effect after recycling are still significantly lower than those in Example 1.
[0065] As shown in Example 1 and Comparative Example 3, Comparative Example 3 employed a stepwise modification method of first pre-modifying with polyHEMAP and then introducing polySBMA. Although this system simultaneously contains phosphorus-containing anchoring groups and zwitterionic segments, they belong to different polymer segments. PolyHEMAP is mainly located on the ZnO surface, while the subsequently introduced polySBMA is difficult to coordinate with the phosphorus-containing anchoring sites within the same segment at the ZnO reaction interface. Therefore, Comparative Example 3 can improve the ZnO surface stability and aqueous interface state to some extent, but the lack of synergistic relationship between its anchoring region and hydration regulation region within the same segment leads to a decrease in its oxytetracycline degradation rate and ZnO degradation rate. 2+ The leaching amount, the actual degradation rate under aqueous matrix interference conditions, and the retention effect during recycling were all lower than those in Example 1.
[0066] As demonstrated in Example 1 and Comparative Example 4, Comparative Example 4 modified the g-C3N4 / ZnO composite photocatalytic substrate using a physical mixture of polyHEMAP and polySBMA. Although this method simultaneously introduces phosphorus-containing groups and zwitterionic segments into the system, polyHEMAP and polySBMA reside in different polymer chains, making it difficult to synchronize their spatial distribution and interaction regions near the ZnO reaction interface. PolyHEMAP primarily plays a local anchoring role, while polySBMA mainly relies on physical adsorption or weak interactions to distribute on the material surface, making it difficult to coordinate with the phosphorus-containing anchoring points for localization near the ZnO surface. In contrast, in Example 1, the HEMAP and SBMA units are located in the same copolymer segment. The HEMAP unit positions the copolymer in the region near the ZnO surface, while the SBMA unit regulates the hydration state and interfacial openness within this localization region. Therefore, the overall photocatalytic performance of Example 1 is superior to that of the physically modified Comparative Example 4.
[0067] As can be seen from Example 1 and Comparative Example 5, the amount of HEMAP-SBMA copolymer added in Comparative Example 5 is significantly higher than that in Example 1. The higher loading of the copolymer allows for more complete coverage of the ZnO surface, thus increasing its Zn content. 2+ The leaching amount was low, and the degradation retention rate remained at a high level under aqueous matrix interference conditions. However, the actual degradation rates of Comparative Example 5 in the blank oxytetracycline system and various aqueous matrix systems were significantly lower than those in Example 1, indicating that excessive organic segments easily form a relatively continuous or thick modified layer on the g-C3N4 / ZnO surface, affecting light penetration, exposure of active sites, and mass transfer of oxytetracycline, dissolved oxygen, and water molecules to the photocatalytic interface. This result shows that this application does not improve material performance by increasing the thickness of the organic modified layer, but rather by forming a low-load, discontinuous, and photocatalytically compatible anchored hydration interface through an appropriate amount of HEMAP-SBMA copolymer.
[0068] As shown in Table 1, Comparative Example 6, the unmodified g-C3N4 / ZnO composite photocatalytic substrate, had its ZnO surface and g-C3N4 / ZnO heterojunction interface not covered by polymer. Therefore, it had sufficient light contact and reactant proximity conditions in the early stages of the reaction, exhibiting a high degradation rate of oxytetracycline after 30 min. This result indicates that the unmodified g-C3N4 / ZnO composite photocatalytic substrate itself possesses good initial photocatalytic activity, and the modification objective of this application is not simply to increase the exposure of initial active sites.
[0069] The degradation rate of Example 1 at 30 min was close to that of Comparative Example 6, indicating that the appropriate amount of HEMAP-SBMA copolymer modification did not significantly obscure the initial photocatalytic interface of g-C3N4 / ZnO. With increasing reaction time, the degradation rate of Example 1 gradually exceeded that of Comparative Example 6, exhibiting a higher oxytetracycline degradation rate at 120 min. Combined with Zn... 2+ The leaching test results show that, due to the lack of interfacial stabilization control on the ZnO surface, Comparative Example 6 is more prone to ZnO surface corrosion and ZnO erosion under aqueous phase, light, and stirring conditions. 2+ Leaching alters the state of the photocatalytic interface near ZnO during subsequent reactions, leading to a decrease in the rate of degradation. In contrast, the HEMAP-SBMA copolymer in Example 1, anchored to the ZnO surface with a low loading, helps maintain interfacial stability during the continuous reaction process, thus exhibiting better sustained degradation performance in the later stages of the reaction.
[0070] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of this application, and are not intended to limit them. Although this application has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some or all of the technical features therein. Such modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of this application.
Claims
1. A method for preparing a composite photocatalytic material, characterized in that, Includes the following steps: S1. Prepare ZnO powder and g-C3N4 powder, mix the ZnO powder and the g-C3N4 powder and calcine them to obtain g-C3N4 / ZnO composite photocatalytic substrate; S2. 2-Methyl-2-acrylate-2-hydroxyethyl ester phosphate and methacryloyl ethyl sulfobetaine were added to a solvent at a molar ratio of 1:3 to 1:10 and mixed. After deoxygenation by passing an inert gas through the solvent, a free radical initiator was added to carry out a copolymerization reaction. After purification and drying, HEMAP-SBMA copolymer was obtained. S3. The g-C3N4 / ZnO composite photocatalytic substrate is dispersed in a solvent, and the HEMAP-SBMA copolymer is added to allow the phosphorus-containing groups in the HEMAP-SBMA copolymer to coordinate and anchor with the Zn sites on the ZnO surface, thereby obtaining an intermediate product; the mass ratio of the g-C3N4 / ZnO composite photocatalytic substrate to the HEMAP-SBMA copolymer is 100:0.5 to 100:5; S4. The intermediate product is subjected to solid-liquid separation. The resulting solid is washed sequentially with water, ethanol or a water-ethanol mixed solvent to remove HEMAP-SBMA copolymers that are not coordinated and anchored to Zn sites on the ZnO surface and weakly adsorbed HEMAP-SBMA copolymers. After washing, the solids are collected by centrifugation, vacuum filtration or filtration, and then vacuum dried to obtain HEMAP-SBMA copolymer modified g-C3N4 / ZnO composite photocatalytic material.
2. The method for preparing a composite photocatalytic material according to claim 1, characterized in that, In step S1, the method for preparing the ZnO powder includes the following steps: Zinc nitrate hexahydrate and urea were dissolved in water to form a mixed solution. The mixed solution was transferred to a hydrothermal reactor and reacted at 180–240°C for 20–30 h. After the precipitate was cooled to room temperature, it was washed repeatedly with pure water and ethanol alternately. After drying, it was calcined at 500–650°C for 1–3 h to obtain ZnO powder. The molar ratio of zinc nitrate hexahydrate to urea was 1:1 to 1:
4.
3. The method for preparing a composite photocatalytic material according to claim 2, characterized in that, The molar ratio of zinc nitrate hexahydrate to urea is 1:
2.
4. The method for preparing a composite photocatalytic material according to claim 1, characterized in that, In step S1, the preparation method of the g-C3N4 powder includes the following steps: Urea was placed in a crucible and calcined at 500–580°C for 1–4 hours. After cooling to room temperature, it was washed several times with pure water and ethanol alternately. Then it was dried in an oven at 55°C for 12 hours and ground evenly in a mortar to obtain g-C3N4 powder.
5. The method for preparing a composite photocatalytic material according to claim 1, characterized in that, In step S1, the mass ratio of ZnO powder to g-C3N4 powder is 1:0.3 to 1, the mixing method is grinding and mixing, and the grinding time is 20 to 60 minutes; the calcination temperature is 450 to 550°C, and the calcination time is 0.5 to 2 hours.
6. The method for preparing a composite photocatalytic material according to claim 1, characterized in that, S2 includes the following steps: 2-Methyl-2-acrylate-2-hydroxyethyl phosphate and methacryloylethyl sulfobetaine were added to a solvent at a molar ratio of 1:3 to 1:10 and stirred to dissolve, thus obtaining a monomer mixture. After purging nitrogen or argon into the monomer mixture to remove oxygen for 30-60 minutes, a free radical initiator is added, and a free radical copolymerization reaction is carried out at 50-80°C for 6-12 hours under inert gas protection to obtain a reaction solution. The reaction solution is subjected to dialysis, ultrafiltration, precipitation or centrifugal washing to remove unreacted monomers and small molecule impurities, and then dried to obtain HEMAP-SBMA copolymer.
7. The method for preparing a composite photocatalytic material according to claim 1, characterized in that, S3 includes the following steps: The g-C3N4 / ZnO composite photocatalytic substrate was added to a solvent and then uniformly dispersed by stirring, sonication, or a combination of stirring and sonication to obtain a substrate dispersion. HEMAP-SBMA copolymer is added to the substrate dispersion, wherein the mass ratio of the g-C3N4 / ZnO composite photocatalytic substrate to the HEMAP-SBMA copolymer is 100:0.5 to 100:
5. The pH of the system is adjusted to 6 to 7.5, and the reaction is carried out at 20 to 40°C for 4 to 8 hours. This allows the phosphorus-containing groups in the HEMAP-SBMA copolymer to coordinate and anchor with the Zn sites on the ZnO surface, and the zwitterionic units of sulfobetaine are distributed on the surface of the g-C3N4 / ZnO composite photocatalytic substrate, thus obtaining an intermediate product.
8. The method for preparing a composite photocatalytic material according to claim 1, characterized in that, S4 includes the following steps: The intermediate product is subjected to solid-liquid separation, and the resulting solid is washed sequentially with water, ethanol or a water-ethanol mixture to remove HEMAP-SBMA copolymers that are not coordinated and anchored to Zn sites on the ZnO surface and weakly adsorbed HEMAP-SBMA copolymers. After washing, the solids are collected by centrifugation, vacuum filtration or filtration, and then vacuum dried at 40-70℃ to obtain HEMAP-SBMA copolymer modified g-C3N4 / ZnO composite photocatalytic material.
9. A composite photocatalytic material, characterized in that, The preparation method according to any one of claims 1 to 8 is obtained.
10. The application of the composite photocatalytic material prepared by the preparation method according to any one of claims 1 to 8 in the photocatalytic degradation of antibiotic wastewater containing oxytetracycline.
Citation Information
Patent Citations
Modification method of super-hydrophilic ZnO for anti-fouling coating
CN114085550A
Medical device and method for manufacturing same
US20220168479A1